Add-on bone scintigraphy after negative radiological skeletal survey for the diagnosis of skeletal injury in children suspected of physical abuse: a systematic review and meta-analysis. Issue 4 (30th September 2020) - Blangis, Flora; Taylor, Melissa; Adamsbaum, Catherine; Devillers, Anne; Gras-Le Guen, Christèle; Launay, Elise; Bossuyt, Patrick M; Cohen, Jérémie F; Chalumeau, Martin
Abstract : Objective(s): To systematically assess the extent to which bone scintigraphy (BS) could improve the detection rate of skeletal injury in children suspected of physical abuse with an initial negative radiological skeletal survey (RSS). Study design: We searched MEDLINE and Web of Science for series of ≥20 children suspected of physical abuse who underwent RSS and add-on BS. We assessed the risk of bias and the heterogeneity and performed random-effects meta-analyses. Results: After screening 1140 unique search results, we reviewed 51 full-text articles, and included 7 studies (783 children, mostly ≤3 years old). All studies were of either high or unclear risk of bias. Substantial heterogeneity was observed in meta-analyses. The summary detection rate of skeletal injury with RSS alone was 52% (95% CI 37 to 68). The summary absolute increase in detection rate with add-on BS was 10 percentage points (95% CI 6 to 15); the summary relative detection rate was 1.19 (95% CI 1.13 to 1.25); the summary number of children with a negative RSS who needed to undergo a BS to detect one additional child with skeletal injury (number needed to test) was 3 (95% CI 2 to 7). Conclusions: From the available evidence, add-on BS in young children suspected of physical abuse with a negative RSS might allow for a clinically significant improvement of the detection rate of children with skeletal injury, for a limited number of BS procedures required. The quality of the reviewed evidence was low, pointing to the need for high-quality studies in this field.